Comparative transcriptome provides insights into gene regulation network associated with the resistance to Fusarium wilt in grafted wax gourd Benincasa hispida - Zhu, Baibi; Li, Chunqiang; Wang, Min; Chen, Jianjun; Hu, Yanping; Huang, Wenfeng; Wang, Huifang (Frontiers in Plant Science, 2023)
Wilt is a soil-borne disease caused by Fusarium that has become a serious threat to wax gourd production. Disease-resistant graft wax gourds are an effective treatment for Fusarium wilt. However, there are few reports on the defense mechanism of graft wax gourd against wilt diseases. In the present study, disease and growth indices were compared between grafted and original wax gourds after infection with Fusarium. High level of disease resistance was observed in the grafted wax gourd, with a lower disease index and low impacts on growth after infection. RNA-seq was performed to identify the differentially expressed genes (DEGs) between the adjacent treatment time points in the grafted and original wax gourds, respectively. The DEG number was higher in grafted group than original group, and the enriched functional categories and pathways of DEGs were largely inconsistent between the two groups. Then a comparative temporal analysis was performed and a total of 1,190 genes were identified to show different gene expression patterns between the two wax gourd groups during Fusarium infection. These genes were enriched in multiple pathways, of which the mitogen-activated protein kinase (MAPK) signaling pathway enhanced the early defense response, and cutin, suberin, and wax biosynthesis signaling pathways enhanced surface resistance in grafted wax gourd in comparison to original group. Our study provides insights into the gene regulatory mechanisms underlying the resistance of grafted wax gourds to Fusarium wilt infection, which will facilitate the breeding and production of wilt-resistant rootstocks.